El Estado Neoconstitucional, la culpabilidad penal y los Wuaoranis:: La motivación penal desde lo constitucional - Pacheco, Mauricio Enrique (2024)
Legal pluralism as a characteristic institution of state constitutional rights neo implementad in Ecuador following the promulgatlon of the Constitution of the Republic in 2008 has remained strong and powerful support from the political discourse but not from the law. lndeed, this constitutional principie needs a regulatory development that should cover mainly in the criminal field, the legal stage of the criminal juslice system, particularly fixed in the framework of criminal responsibility. The theory of crime when studying the category of substance Guilt is a job for the state to molivate people from the field of the development of elhical consciousness legal compllance to legal regulations. A well concientizada population by the Slate on the scope and consequences of !he criminal law implies a two-way relationship with the populalion that constitutes. An unmotivated or, even worse, oblivious to society and back lo state conglomerate is a segment who respect the motivation of the criminal law has never gonna get. But even when they have been they who lhey have given up part of the social contract as the basis of peaceful coexistence, as ín !he case of Amazonian indigenous Taraomenane and part of the Huaorani.